Vasoactive Intestinal Peptide-Secreting Pancreatic Neuroendocrine Tumor: A Case Report - Sritharan, T.; Suganthan, N.; Sujanitha, V.; Sutharshan, V. (Springer, 2022)
A 36-year-old female with chronic watery diarrhea and persistent hypokalemia for more than eight months duration eventually being diagnosed as vasoactive intestinal peptide tumor (VIPoma) clinically and histologically is presented here. The patient achieved complete recovery after starting octreotide, a somatostatin analog. She underwent a distal pancreatectomy along with the removal of the tumor at Teaching Hospital Jaffna for the permanent cure.
Keywords: Chronic diarrhea; Distal pancreatectomy; Octreotide; Hypokalemia; Vasoactive intestinal peptide tumor